Heart Attack Monitoring by Heartbeat Sensing using IoT - Tripathi, Raghvendra Narain (Indian Journal of Computer Science, 2019)
Three heart attacks can kill a person but a heart attack can kill a person first time it strikes. If we check our heart daily, we can identify this disease early. Life is precious. Many people around us lose their life because of heart disease. The factors which cause heart attack are less physical work, unhealthy diet, and age. To minimize the impact of this disease on our society, we are developing an arrangement which can reduce deaths caused by heart attack and we can also find whether a person is suffering from heart problems or not. The recommended system is a heart attack checker which will tell whether a person is having a heart attack or not and we are doing this with the help of IoT. The sensors which are inside the system are joined to the controller that helps in checking the heat rate and sending the result to the internet. The user sets the bar of the heartbeat of the patient as high or low. After this he starts measuring the heartbeat of the patient. The device sends an alarm to the user when the heartbeat crosses the bar of high or low. For doing this work our arrangement has two parts. First part is the sending part which is present in the patient and the other part is the receiving part which is present in the office of the doctor. The arrangement uses a heartbeat sensor to know the level of the heartbeat of the patient and displays the result on the monitor of the room.